Cognitive neuroscience: early learning centres. - Johansen-Berg, H; Walsh, V (2001)
Learning leads to neural changes often considered to be driven by 'smart' areas of the brain. A recent study of the cellular changes that underlie perceptual learning has found that plasticity in the primary visual cortex V1 is necessary for learning and the changes that correlate with learning are more complex than one might expect.